2020
DOI: 10.5935/2595-0118.20200050
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of chronic lower back pain risk in women: population-based study

Abstract: BACKGROUND AND OBJECTIVES:Low back pain is a common condition in women. In addition to that, women have a higher risk of chronic pain. However, the factors associated with chronic low back pain are still controversial. Thus, this study's objective was to evaluate the predictive factors associated with a higher risk of chronic low back pain. METHODS: A cross-sectional population-based study was conducted on a sample of 636 Brazilian adult women aged 20-69 years who reported symptoms of low back pain in the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
1
1
0
2
Order By: Relevance
“…According to the SBST scale, most students (82%) had low risk of chronicity, whereas 14% and 4% had medium and high risk, respectively. According the literature 19 , these findings confirm that physical factors interfere the most with low back pain. Individuals with a low risk of chronicity have good prognosis, even more when compared with medium and high risk chronicity levels, as probably psychosocial factors are involved in pain 9 .…”
Section: Table 2 Continuationsupporting
confidence: 66%
See 1 more Smart Citation
“…According to the SBST scale, most students (82%) had low risk of chronicity, whereas 14% and 4% had medium and high risk, respectively. According the literature 19 , these findings confirm that physical factors interfere the most with low back pain. Individuals with a low risk of chronicity have good prognosis, even more when compared with medium and high risk chronicity levels, as probably psychosocial factors are involved in pain 9 .…”
Section: Table 2 Continuationsupporting
confidence: 66%
“…The prevalence of low back pain is associated with several causes and factors, such as sedentary lifestyle and obesity 17,18 . A study with women southern Brazil revealed that sedentary lifestyle was the greatest factor of association with chronic low back pain 19 . Another study, conducted in the state of São Paulo, showed that women who did some kind of physical activity had better quality of life and relief of low back pain 20 .…”
Section: Table 2 Continuationmentioning
confidence: 99%
“…A prevalência de dor lombar está associada a diversas causas e fatores, como sedentarismo e obesidade 17,18 . Um estudo com mulheres de uma cidade do Sul do Brasil revelou que o estilo de vida sedentário foi o maior fator de associação à dor lombar crônica 19 . Outro estudo, realizado em uma cidade no estado de São Paulo, mostrou que mulheres que faziam algum tipo de atividade física tinham melhor qualidade de vida e alívio da dor lombar quando comparadas àquelas que não faziam nenhuma atividade 20 .…”
Section: Discussionunclassified
“…Segundo a escala SBST, a maioria dos estudantes (82%) foram classificados com baixo risco de cronicidade, enquanto 14% e 4% foram classificados com médio e alto riscos, respectivamente. Estes achados estão de acordo com a literatura 19 e confirmam que o que mais interfere na dor lombar são os fatores físicos. Os indivíduos com baixo risco de cronicidade apresentam um bom prognóstico, ainda mais comparados aos níveis de cronicidade de médio e alto risco, pois provavelmente há fatores psicossociais envolvidos na dor 9 .…”
Section: Discussionunclassified